Demographic and clinical impact on preoperative BREAST-Q ePROM completion and baseline outcomes in women undergoing breast cancer surgery: a quantitative descriptive study at a Danish university hospital - Karin Piil; Volker Jürgen Schmidt; Stine Thestrup Hansen; Lone Bak Hansen; Anna Mejldal; Julie Hougaard Prüsse; Lotte Gebhard Ørsted (BMJ Open)
Objectives This study aimed to investigate patients’ use of electronic Patient-Reported Outcome Measures (ePROMs) and understand the demographic and clinical factors that may be correlated with patient responses to the BREAST-Q at the preoperative stage of breast cancer. The BREAST-Q is a PROM in questionnaire format, developed and validated to assess satisfaction and quality of life for breast surgery patients.The hypothesis tested is that considering disparities in geography, age and education among responders is essential for capturing a diverse patient population in future Patent-Reported Outcome Measures initiatives, examining how these characteristics are associated with Patent-Reported Outcome Measures utilisation and outcomes.Design Quantitative descriptive study.Setting Electronic Patient-Reported Outcome Measures were collected between 6 September 2021 and 5 September 2022 from patients recruited from an outpatient clinic at a Plastic- and Breast Surgery Department at a University Hospital in Denmark.Participants Participants include a total of 629 Danish-speaking women diagnosed with breast cancer and scheduled for breast cancer surgery, with a final participation rate of 468.Intervention Preoperative ePROMs and demographic data were collected between September 2020 and 2021 through patients’ secure national digital post-box.Main outcome measures Demographic variables of both responders and non-responders were assessed using t-tests, Mann-Whitney U tests and χ2 tests. Linear regression models were employed to determine the demographic variables associated with BREAST-Q subscale scores.Results The response rate for ePROMs was 72.5% with a median age of responders at 62 years. Older patients reported lower breast satisfaction (unadjusted coefficient bu=−0.26 (95% CI −0.44; −0.07), p=0.006) but better physical well-being (adjusted coefficient ba=0.23 (0.08; 0.37), p<0.001). Lower educational achievement was correlated with reduced breast satisfaction and psychosocial and sexual well-being; for example, patients with a master’s/doctoral level education scored 14.29 points higher in psychosocial well-being (95% CI 6.50; 22.07, p<0.001) compared with those with lower secondary education. Cohabiting patients reported psychosocial well-being scores approximately four points higher than those living alone (ba=3.91 (0.06; 7.75), p=0.046). Body mass index (BMI) was negatively associated with sexual well-being, with a 0.75-point decline per additional BMI point (ba=−0.75, (-1.12; −0.37), p<0.001).Conclusions The present study demonstrates a positive attitude towards completing BREAST-Q as ePROMs among women diagnosed with breast cancer in the investigated region in Denmark. However, completion rates for ePROMs varied by demographic factors such as age, marital status and access to healthcare. Younger, more educated, married patients with lower BMI who lived near major cities were more likely to report better pretreatment outcomes.